2003
DOI: 10.1128/cdli.10.3.426-430.2003
|View full text |Cite
|
Sign up to set email alerts
|

T- and B-Cell Immune Responses of Patients Who Had Undergone Colectomies to Oral Administration of Salmonella enterica Serovar Typhi Ty21a Vaccine

Abstract: The capacity of an oral live attenuated Salmonella enterica serovar Typhi Ty21a vaccine to induce immune responses in patients who had undergone colectomies because of ulcerative colitis was evaluated, and these responses were compared with those of healthy volunteers. Purified CD4 ؉ and CD8 ؉ T cells from peripheral blood were stimulated in vitro by using the heat-killed Ty21a vaccine strain, and the proliferation and gamma interferon (IFN-␥) production were measured before and 7 or 8 days after vaccination. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…These results were confirmed by others [10,29,30]. We have demonstrated that PBMCs from Ty21a and CVD 909 vaccine recipients also secreted IL-1b, TNF-a, and IL-10 after in vitro incubation with S. Typhi flagella [14,19].…”
Section: Both Cd4 + Helper T Cells and Cd8 + Cytotoxic T Cells Might supporting
confidence: 91%
See 1 more Smart Citation
“…These results were confirmed by others [10,29,30]. We have demonstrated that PBMCs from Ty21a and CVD 909 vaccine recipients also secreted IL-1b, TNF-a, and IL-10 after in vitro incubation with S. Typhi flagella [14,19].…”
Section: Both Cd4 + Helper T Cells and Cd8 + Cytotoxic T Cells Might supporting
confidence: 91%
“…Moreover, we identified CD3 + CD4 + CD8 Ϫ CD56 Ϫ T helper cells as the predominant IFN-g-secreting effector cell population responding to soluble S. Typhi antigens in CVD 908-htrA [6] and CVD 909 vaccine recipients (figure 1A and 1B) (R. Wahid, R. Salerno-Gonçalves, and M.B.S., unpublished data). Lundin et al [10] and Kilhamn et al [29] reported that both CD4 + and CD8 + T cells from Ty21a vaccine recipients secrete IFN-g in response to particulate S. Typhi antigens.…”
Section: Both Cd4 + Helper T Cells and Cd8 + Cytotoxic T Cells Might mentioning
confidence: 98%
“…[28][29][30][34][35][36][37] Studies of other vaccines in IBD have shown impaired adaptive immunity to vaccination, including impaired antibody responses to tetanus toxoid booster in adults with IBD, and to oral cholera and S. typhi vaccinations in adults with ulcerative colitis postcolectomy. [38][39][40][41] Impaired immune response to the pneumococcal polysaccharide vaccine in adults with IBD on immunosuppressive therapies has also been reported. 42 Therefore, immune dysregulation inherent to IBD or from immunosuppressive medications or surgical resections altering anatomical exposures to oral vaccines may weaken immune responses to a variety of vaccines in IBD.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, a handful of promising new attenuated oral typhoid vaccine candidates have been developed by our group and others that exhibit low reactogenicity and broad immunogenicity, encompassing a wide array of CMI responses including increased proliferative responses and cytokine production (particularly IFN-γ, tumor necrosis factor-α, and IL-10), as well as classical and non-classical class I-restricted cytotoxic T cell activity to purified S. Typhi antigens and S. Typhi-infected cells. 46,8,9,11,14,15,17–19,21–23,25,37 These responses are likely to play an important role in the host defense against S. Typhi by several mechanisms, including enhancement of the bactericidal activity of cells of the innate immune response (e.g., macrophages) and antigen presentation, killing of S. Typhi-infected cells, and providing help for antibody responses to S. Typhi antigens. 46,8,22,23,25,38,39 …”
Section: Discussionmentioning
confidence: 99%